Investigation of a new energy system for clean methanol production. (6th April 2020) - Ishaq, Haris; Dincer, Ibrahim
Summary: This study develops a novel system for renewable energy based methanol production in a clean way. The proposed system employs solar heliostat and solar PV subsystems for hydrogen, cooling and power production. The solar heliostat field, thermochemical copper‐chlorine (Cu‐Cl) cycle, refrigeration, methanol production and methanol separation are the major components in the proposed system. First, clean hydrogen is produced via a four‐step thermochemical Cu‐Cl cycle which is further synthesized into methanol. The proposed configuration is investigated under both energy and exergy analyses and software package of Engineering Equation Solver and Aspen Plus are employed for modeling and simulation. The performance index is calculated in terms of efficiencies, and the calculated overall energy and exergy efficiencies are 37.58% and 36.8%. The energetic and exergetic efficiencies of the Cu‐Cl cycle are found to be 39.6% and 43.5% respectively. Further sensitivity results are presented and discussed in this study. Abstract : A novel design for renewable energy based methanol production in a clean way. The developed system offers the methanol production of 86.9 kg/h. The amount of power produced by the system after meeting the requirement is 641 kW. Energy and exergy efficiencies of overall system are found to be 37.58% and 36.8%.